PENGARUH CEO OWNERSHIP, CEO EXPERT POWER, DAN STRUKTUR KEPEMILIKAN KELUARGA TERHADAP TINGKAT PENGHINDARAN PAJAK (Studi Empiris: Perusahaan Sektor Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2023) - Betta Maulyda Kusumaning Putri; Imam Ghozali (Diponegoro Journal of Accounting, 2025)
This study aims to examine the effect of CEO ownership, CEO expert power, and family ownership structure on the level of tax avoidance rate in property and real estate sector companies listed on the Indonesia Stock Exchange in 2020-2023. This study used a multiple regression model with three control variabels, such as company size, return on assets, and leverage. This study used secondary data obtained from the company’s annual report published from 2020-2023 consistently. The research’s sampling method was purposive sampling with certain criterias. There were three hypotheses tested using coefficient of determination test, simultaneous significance (F test), and significant individual parameters (t-test). This study found that CEO ownership has a negative and significant effect on the level of tax avoidance. CEO expert power has a positive and significant effect on the level of tax avoidance. Meanwhile, family ownership structure has an insignificant effect on the level of tax avoidance. The insignificant effect of family ownership structure is caused by the data on company size, return on assets, and leverage which are quite varied.